The redemption : an interdisciplinary symposium on Christ as Redeemer - Davis, Stephen T., 1940-; Kendall, Daniel; O'Collins, Gerald (Oxford ; New York : Oxford University Press, 2004)
"Twenty-four scholars from different universities, churches, and continents have worked on this book - a volume on the central Christian belief: the redemption of human beings through Jesus Christ"--Provided by Publisher.
Redemption : some crucial issues / Gerald O'Collins -- Biblical questions -- Reconciliation and the plain sense witness of scripture / Christopher Seitz -- Paul and the metaphors for salvation :some reflections on Pauline soteriology / Gordon D. Fee -- Redemption from the new perspective : towards a multilayered Pauline theology of the cross / N.T. Wright -- God made Christ to be sin (2 Corinthians 5: 21) : reflections on a Pauline paradox / Jean Nol Aletti -- Israels redeemer is the one to whom and withwhom she prays / Peter Ochs -- Patristic and medieval periods -- He himself is our peace (Eph. 2: 14) : early Christian views of redemption in Christ / Brian Daley -- The power in the blood : sacrifice, satisfaction, and substitution in late medieval soteriology / Caroline Walker Bynum -- Foundational and systematic issues -- Narrative and the problem of evil : suffering and redemption / Eleonore Stump -- Karma or grace / Stephen T. Davis -- Catholic Protestant views of justification : how should Christians view theological disagreements? / C. Stephen Evans -- The redemption practised and proclaimed -- Graven with an iron pen : the persistence of redemption as a theme in literature / Robert Kiely -- Images of redemption in art and music / David Brown -- The redemption of the created order : sermons on Romans 8 / Marguerite Shuster.
Includes bibliographical references and index.
Keywords: Jesus Christ -- Person and offices -- Congresses; Redemption -- Congresses